1994
DOI: 10.1111/j.1528-1157.1994.tb02909.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal Cerebral Magnetic Resonance Changes Associated with Partial Status Epilepticus

Abstract: We report 2 patients with transient abnormalities on magnetic resonance imaging (MRI) associated with partial status epilepticus (SE). A man with a 4-month history of partial seizures had complex partial SE for 9 days, with left temporal maximum on ictal EEG. Left temporal lobe T2 signal was increased on MRI during SE, but cerebral MRI was normal 9 weeks later. A woman with "cryptogenic" temporal lobe epilepsy for 16 years had complex partial SE for 1 week, with right temporal maximum on ictal EEG. T2 Signal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 26 publications
(24 reference statements)
5
29
0
7
Order By: Relevance
“…[20][21][22][23][24] The resolution of the signal changes within 3 months, as seen in our patient, has been also reported in several other studies. 21,22,25 The signal hyperintensity may or may not be associated with gadolinium contrast enhancement and does not exhibit mass effect.…”
Section: Series Of 34 ML Steam (Echo Time 20 Msec) Spectra Obtainesupporting
confidence: 70%
See 1 more Smart Citation
“…[20][21][22][23][24] The resolution of the signal changes within 3 months, as seen in our patient, has been also reported in several other studies. 21,22,25 The signal hyperintensity may or may not be associated with gadolinium contrast enhancement and does not exhibit mass effect.…”
Section: Series Of 34 ML Steam (Echo Time 20 Msec) Spectra Obtainesupporting
confidence: 70%
“…[20][21][22][23][24] The resolution of the signal changes within 3 months, as seen in our patient, has been also reported in several other studies. 21,22,25 The signal hyperintensity may or may not be associated with gadolinium contrast enhancement and does not exhibit mass effect. 23,24 Proposed mechanisms for these lesions include vasogenic edema reflecting altered permeability of the vessels in relation to seizures, which results in a breakdown of the bloodbrain barrier and fluid accumulation in the white matter within the extracellular space.…”
Section: Series Of 34 ML Steam (Echo Time 20 Msec) Spectra Obtainesupporting
confidence: 70%
“…All the findings completely resolved upon follow-up 2 months later. Although similar findings have been reported in recent years (1,3,5,7,8), there are few reports referring to the MRA findings due to the status epilepticus (2). We want to indicate the reversible radiological alterations in MRA.…”
Section: Discussionsupporting
confidence: 48%
“…Many reports have demonstrated that nonconvulsive status epilepticus or frequent partial seizures may produce transient cortical edema, T2 hyperintensity, leptomeningeal or cortical enhancement, and permanent sequelae, including cortical laminar necrosis. [6][7][8][9] Postictal MR imaging findings in patients without prior radiation therapy appear different from SMART, suggesting that SMART may represent a unique syndrome with a complex poorly understood pathophysiology occurring in a subset of patients long after radiation therapy. 10,11 It may be that seizures in patients with SMART strain an already impaired brain because of the chronic endothelial vascular damage caused by remote radiation, and this "double hit" produces infarction in some instances in the affected cortical areas.…”
Section: Discussionmentioning
confidence: 99%